Is There a Positive Side to T Cell Exhaustion? - Pawelec, Graham (Frontiers in Immunology, 2019)
T cell exhaustion describes a state of late-stage differentiation usually associated with active prevention of functionality via ligation of negative signalling receptors on the cell surface. Although often confused with cellular senescence, it differs in that the state is not permanent and can be reversed by modulating signalling by these negative receptors. This is desirable in immunotherapy for cancer and possibly certain infectious disease, but reciprocally inducing and maintaining this state, or some aspects of it, may be beneficial in organ transplantation and autoimmunity. Even under physiological non-pathological conditions, T cell exhaustion may play a role in the retention of T cell clones required for immunosurveillance, and prevent their loss via elimination at the Hayflick limit. This essay briefly reviews T cell exhaustion in contrast to replicative senescence, and circumstances under which its modulation may be beneficial.